Hubungan Asupan Zat Gizi Besi Dengan Kadar Hemoglobin Remaja Putri - Natalia Kristin; Lewi Jutomo; Daniela L.A Boeky (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Iron nutrition is the main element in the formation of hemoglobin. Consumption of insufficient iron nutrient intake can be at risk of anemia which causes oxygen transport to be reduced, resulting in low energy production which has an impact on the work productivity of young women. This study aims to determine the relationship between iron nutrient intake and hemoglobin levels of students of the Faculty of Public Health, Nusa Cendana University. This type of research is an analytical survey and is used in a cross sectional design. The total population of 595 female students and a sample of 86 female students consisting of semesters II, IV, and VI were obtained. Sampling is carried out by the stratified sampling method purposively. Statistical analysis using the Pearson Product Moment test. The results showed that out of 86 respondents, the average consumption of iron intake was 11.5 mg and 76.7% of female students' hemoglobin levels were in the normal category. The results of the Pearson Product Moment analysis showed that the p-value= 0.965>0.05 had no significant relationship between the level of iron nutrition adequacy and hemoglobin levels in young women. The need to provide education about the importance of consuming iron nutrition intake to prevent the risk of anemia.